Reliability and validity of the K-force grip dynamometer in healthy subjects: do we need to assess it three times? - Magni, Nico; Olds, Margie; McLaine, Sally (Hand therapy, 2023)
Introduction Digital dynamometers to assess grip strength are becoming more common in research and clinical settings. The aim of the study was to assess validity and reliability of the K-force dynamometer compared to the Jamar dynamometer. We also aimed to assess differences over the course of three measurements. Methods Twenty-seven healthy participants were included. Three trials with the K-force and Jamar dynamometers were completed. Testing order was randomised. Intraclass correlation coefficients (ICCs) with absolute agreement assessed reliability and validity. Standard error of the measurement (SEM) and minimal detectable change (MDC95) were calculated. Concurrent validity was assessed using Pearson’s correlations and ICCs. Differences between the three repetitions were assessed using one-way repeated measures ANOVAs. Results Both the K-force and the Jamar presented excellent intra-rater reliability with ICCs ranging from 0.96 to 0.97. The SEM ranged from 1.7 to 2 kg and the MDC from 4.7 to 5.7 kg for both dynamometers. The concurrent validity of the K-force was high (r ≥ 0.89). However, the K-force underestimated the grip strength by 4.5–8.5 kg. There was no change in grip strength with either dynamometer over the course of three trials. Conclusions: The K-force is reliable, but it underestimates grip strength by 4.5–8.5 kg compared to the Jamar dynamometer. K-force can be used to monitor progress over time but cannot be used to compare results against normative data. The use of a single measurement when assessing grip strength is sufficient when assessing healthy subjects.